STYLISTIC FEATURES OF WINGED EXPRESSIONS (Eureka Journal of Humanities and Social Research, 2026)
Identifying the features of the stylistic use of winged expressions in a literary text is of great importance. This article examines the common usage of Latin and French winged expressions in texts. Their functions are revealed through analysis.
Keywords: Winged expression, quotation, implicit, explicit, precise, imprecise, author, source, function, analysis.